A STREAMLINED ELDER MISTREATMENT CARE MODEL FOR HOSPITAL EMERGENCY DEPARTMENTS. (11th November 2018) - Dyer, C B; Mosqueda, L; Lachs, M S; Bonner, A; Rosen, A E; Olsen, B; Sivers-Teixeira, T; Burnett, J
Abstract: The National Collaboratory to Address Elder Mistreatment developed a streamlined care model for addressing elder mistreatment in emergency department settings. This presentation will describe the core elements of the care model as well as present methods and findings related to prototyping and feasibility testing. The care model was developed based on findings from an environmental scan and formative research interviews to promote triaging older patients based on their level of risk. Tools developed to facilitate improved practices include an emergency department assessment profile, a training curriculum, as well as guidelines for screening, intervention, follow-up and collaboration with community resources. The authors used results from feasibility testing of the core elements with community partners to refine the elements and revealed key considerations for implementation. Authors will discuss the development of the core elements, including results from prototype testing and clinical partner feedback.